“La suavidad de Artemisa”: reflections on the reception of Artemisia Gentileschi in Spain - Jesse Locker (Boletín del Museo del Prado)
Two wax busts depicting a man and a woman, with authentic clothing and hair, once part of the Royal Collections and recently placed on display in the Museo del Prado, were previously ascribed to Giovanni Francesco Pieri, a Tuscan wax modeller active in Naples. Thanks to documentation hitherto not linked to them, the author proposes to attribute the busts to Filippo Scandellari, the first artist to create realistic wax portrait busts in his birthplace of Bologna. Although these works were intended for private collecting, from the late eighteenth century onwards in Spain there was also a widespread trend for organising popular exhibitions of wax figures, often by Italian artists and entrepreneurs, of whom this article provides an overview, with a particular focus on wax portraits of Spanish royalty.